2015
DOI: 10.1016/j.celrep.2015.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Drives Th17 Cell Differentiation by Inducing the Lipid Metabolic Kinase, ACC1

Abstract: Chronic inflammation due to obesity contributes to the development of metabolic diseases, autoimmune diseases, and cancer. Reciprocal interactions between metabolic systems and immune cells have pivotal roles in the pathogenesis of obesity-associated diseases, although the mechanisms regulating obesity-associated inflammatory diseases are still unclear. In the present study, we performed transcriptional profiling of memory phenotype CD4 T cells in high-fat-fed mice and identified acetyl-CoA carboxylase 1 (ACC1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
175
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 192 publications
(208 citation statements)
references
References 55 publications
19
175
2
2
Order By: Relevance
“…Both pathways are required for the early and full activation and metabolic reprogramming of naive or memory CD4 + T cells in murine and human systems. Consistent with our findings, hyperlipidemia caused by obesity or atherogenic conditions exhibited an increased frequency of CD44 hi population among the CD4 + T cells4045. Highly proliferating cells including activated T cells appear to require large amounts of fatty acids.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Both pathways are required for the early and full activation and metabolic reprogramming of naive or memory CD4 + T cells in murine and human systems. Consistent with our findings, hyperlipidemia caused by obesity or atherogenic conditions exhibited an increased frequency of CD44 hi population among the CD4 + T cells4045. Highly proliferating cells including activated T cells appear to require large amounts of fatty acids.…”
Section: Discussionsupporting
confidence: 90%
“…We previously reported that extrinsic fatty acid supplementation restored the function of Acaca −/− Th17 cells40. Those data led us to postulate that cellular fatty acid was limiting in TOFA-treated or GW9662-treated CD4 + T cells in the early activation phase.…”
Section: Resultsmentioning
confidence: 92%
“…We also show that the frequency of IL‐23R expressing T helper cells is increased by combined hypercholesterolemia and hyperlipidemia, a finding consistent with increased Th17 generation in hyperlipidemic mice 14. Focusing on CD4 + T cells, IL‐23R expression was found to be largely restricted to CCR6 + cells with an effector memory (CD44 hi CD62 low ) phenotype that is consistent with IL‐23R expressed in antigen‐experienced Th17 cells 15…”
Section: Discussionsupporting
confidence: 68%
“…RORC (RAR-Related Orphan Receptor C) regulates production of the inflammatory cytokine IL-17 by T helper-17 (Th17) cells; Th17 cell activation and cytokine production appears to play a critical role in the pathogenesis of diabetes (37-41). Additionally, genetic variation in RORC has been linked to body fat composition levels in cattle (42).…”
Section: Discussionmentioning
confidence: 99%